MPO-ANCA-associated necrotizing glomerulonephritis in rheumatoid arthritis; a case report and review of literature - Mário Góis; Ana Messias; Dulce Carvalho; Fernanda Carvalho; João Sousa; Helena Sousa; Fernando Nolasco (Society of Diabetic Nephropathy Prevention, 2017)
Background: Renal involvement in rheumatoid arthritis (RA) is common and has a negative impact on patient survival. Only few cases have been reported of necrotizing glomerulonephritis (GN) associated with myeloperoxidase anti-neutrophil cytoplasmic antibody (MPO-ANCA) in patients with RA. Case Presentation: We report a patient with RA who developed a necrotizing GN associated with ANCA-MPO, treated with rituximab (RTX). A 55-year-old man with a 27-year history of RA under secukinumab was referred to our nephrology clinic with worsening renal function associated with microhematuria and proteinuria. Our laboratory evaluation showed hypocomplementemia and positive titers for MPO-ANCA (615 U/mL). A renal biopsy demonstrated pauci-immune necrotizing GN. The patient was treated with 3 consecutive pulses of methylprednisolone followed by oral prednisolone (1 mg/Kg) and rituximab (1000 mg, repeated 14 days later). After a 10-month follow-up, the arthritis remains well-controlled, renal function stabilized, proteinuria improved and MPO-ANCA titer normalized (6.3 U/mL). Conclusions: Necrotizing GN is a rare but a serious condition and an early diagnosis is essential to treatment. This is the first case of necrotizing GN (without extra-renal manifestations of vasculitis) in a patient with active RA, successfully treated with RTX.